Publisher Correction: Effect of Nonuniform Perpendicular Anisotropy in Ferromagnetic Resonance Spectra in Magnetic Nanorings (Scientific Reports, 2021 11 1 14230 10.1038/S41598-021-93597-8) - Saavedra-Díaz, E (Nature Research, 2021)
The original version of this Article contained an error in the Results and analysis section, under the subheading ‘Dynamic magnetic properties’, where the unitary vector “ ˆn ” did not display correctly. This error has now been corrected in the PDF version of the Article; the HTML version was correct from the time of publication. © The Author(s) 2021